Assessing Apparently Equivalent Translations in the News Media - Conway, Kyle (Meta, 2005)
AbstractThis essay represents a preliminary attempt to devise a method for examining words and their apparently equivalent translations as they appear in the news media. Taking Walter Benjamin’s essay on the task of the translator as a starting point and drawing on Edmund Husserl’s phenomenology and Antoine Culioli’s and Paul Laurendeau’s enunciative linguistics, the author argues that this appearance of equivalence is deceptive, for at least two reasons: first, because differing, culturally specific assumptions underlie the interpretations of these words and their translations; and second, because as the implications of these words and their translations are reported upon and contested (by political actors, by reporters, by editorialists), their meanings effectively change.